Understanding the Factors Influencing the Number of Extracurricular Clubs in American High Schools - Tang Amy; Wang Yang; Tang Chunqiang (Open Education Studies)
Previous research has provided compelling evidence of a strong connection between extracurricular activities and positive youth development. While both school offerings and student participation affect the outcomes of extracurricular activities, earlier studies have primarily focused on student participation. In contrast, this study shifts the focus to school offerings. We extensively collect lists of extracurricular clubs offered by hundreds of American high schools and analyze the relationship between schools’ club counts and various factors, such as school enrollment, household income, pupil-to-teacher ratio, and racial demographics. We find that, although the relationship exhibits complex higher-order effects and nonlinearity, it can still be effectively captured by our carefully constructed predictive model. Moreover, we find that, despite the significant influence of school demographics, schools still have ample opportunities to take the initiative to improve their club offerings.